2022
DOI: 10.1016/j.bioactmat.2021.05.046
|View full text |Cite
|
Sign up to set email alerts
|

In vivo urinary compatibility of Mg-Sr-Ag alloy in swine model

Abstract: A biodegradable metallic ureteral stent with suitable mechanical properties and antibacterial activity remains a challenge. Here we reveal the scientific significance of a biodegradable Mg-Sr-Ag alloy with a favorable combination of balanced mechanical properties, adjustable indwelling time in urinary tract and evident antibacterial activity via in vivo experiments in a swine model. Attributed to the rheo-solidification process, equiaxial microstructure and significantly refined grains (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Comprehensively considering the cell growth and osteogenic differentiation, the Mn-containing Mg–6Zn alloy is more suitable than the Mn-free alloy as a bone implant. In addition to being used as a bone implant, there are also studies on the use of biodegradable magnesium alloys as ureteral stents …”
Section: Resultsmentioning
confidence: 99%
“…Comprehensively considering the cell growth and osteogenic differentiation, the Mn-containing Mg–6Zn alloy is more suitable than the Mn-free alloy as a bone implant. In addition to being used as a bone implant, there are also studies on the use of biodegradable magnesium alloys as ureteral stents …”
Section: Resultsmentioning
confidence: 99%
“…In 2021, Tie et al innovatively developed the Mg-Sr-Ag alloy, combining the exceptional mechanical properties of the Mg-Sr alloy with the pronounced antimicrobial activity of silver (Ag). They validated its biocompatibility and impact on the urological system ( Tie et al, 2022 ). Previously, they had preliminarily confirmed the applicability of the Mg-Sr alloy for the manufacture of biodegradable bone fixation devices and demonstrated the pronounced antibacterial activity of magnesium alloys containing silver in an in vitro setting ( Tie et al, 2013 ; Tie et al, 2016 ).…”
Section: Technology Applied To the Development Of Busmentioning
confidence: 99%
“…In 2022, Tie et al fabricated Mg-1.0Sr-0.5Ag (wt.%) alloy (JQ alloy) through semi-solid rheo-extrusion ( Tie et al, 2022 ). Their experimental results demonstrated a 111% increase in ultimate tensile strength for JQ alloy (223.7 MPa) compared to pure magnesium (105.9 MPa).…”
Section: Future Clinical Applications Of Busmentioning
confidence: 99%
“…Tie et al examined biocompatibility of an antibacterial biodegradable metallic ureteral stent (magnesium-strontium-silver alloy) that showed a significant reduction in colony forming units in the urine compared to magnesium stents at 6 and 12 weeks in a swine model [24]. Although complete degradation was not achieved at the end of the 12-week study period [24]. An ideal biodegradable stent needs to maintain patency and stability for the first 1–2 weeks with subsequent quick and reliable degradation time.…”
Section: Reducing Stent-associated Symptomsmentioning
confidence: 99%
“…Most recent animal model studies have demonstrated limited success of biodegradable stents with variable degradation time (either degrading too fast or too slow), increased biofilm formation and bacteriuria [22,23]. Tie et al examined biocompatibility of an antibacterial biodegradable metallic ureteral stent (magnesiumstrontium-silver alloy) that showed a significant reduction in colony forming units in the urine compared to magnesium stents at 6 and 12 weeks in a swine model [24]. Although complete degradation was not achieved at the end of the 12-week study period [24].…”
Section: Biodegradable Ureteral Stentsmentioning
confidence: 99%